Assessing Local Government Policy Implementation for Improving Educational Quality in Coastal Communities - Sari, Eka Nofia; Apriani, Fajar; Indarto, Kus; Fagbamila, Akinwumi Samuel (JED (Jurnal Etika Demokrasi), 2026)
This study addresses the persistent inequality in educational quality between coastal and non-coastal regions, where geographic isolation, fragile local economies, and limited public services systematically undermine access to and outcomes of schooling. It specifically analyzes how local government policy is implemented to improve education quality in coastal areas, with particular attention to institutional capacity, governance dynamics, and multi-stakeholder engagement. A qualitative, exploratory research design was employed, combining in-depth interviews with local officials, school leaders, teachers, community figures, and parents, along with field observations and analysis of policy documents and program reports. Data were analyzed through thematic coding and constant comparison, and their credibility was reinforced using source and method triangulation. The findings show that successful policy implementation is strongly shaped by the capacity of local governments to translate national regulations into context-sensitive programs, coordinate relevant actors, and institutionalize collaborative mechanisms with communities, educational institutions, and non-governmental organizations. However, weak inter-agency synergy, inadequate infrastructure, teacher shortages, and low community participation remain critical barriers to improving educational quality in coastal settings. The study concludes that an adaptive, participatory, and locally grounded policy approach is essential to ensure the sustainability and equity of education quality in coastal areas. The novelty of this research lies in its integrated focus on institutional capacity, governance practices, and multi-actor collaboration within the specific socio-geographic context of coastal communities. The results contribute empirically and conceptually to the literature on decentralized education governance and provide practical guidance for local policymakers seeking to reduce territorial disparities in education.